Creative Ethnoscience on Rice Barn Artifacts of the Bayan Beleq Community, North Lombok: Etnosains Kreatif pada Artefak Lumbung Padi Masyarakat Bayan Beleq, Lombok Utara - Sri Aprilia Nur Larasati; Safariyanti Manisa; Yeni Ainiyawati; I Gede Darma Winata; Fazza Firjatullah Al-khulaifi; Febriyanti Istikomah (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
The application of the concept of ethnoscience is basically inseparable from culture, it is necessary to develop an information medium and learning by applying an ethno-scientific approach. The aim is to introduce and preserve scientific values related to local culture, especially artifacts from the rice barns of the Bayan Beleq community in North Lombok. The method used in collecting data in this study uses observation, interviews and documentation. The results of the research are that the process of building rice barns is not made haphazardly and must pay attention to several scientific aspects such as, selecting wood that is strong and termite resistant, placing the barn which must face west to get sufficient sunlight so that the room temperature is not humid and avoids the growth of fungi which can damage the quality of rice. This research is relevant as a culture-based science learning medium that can connect scientific concepts with local wisdom, while also supporting the preservation of traditional heritage.